The Principle of Non Discrimination Against the Unilateral Determination of Payment Method Provisions in Non Cash Buying and Selling Transactions - Alizcia Dora Parhusip; Iwan Erar Joesoef (PALAR (Pakuan Law review), 2026)
References A. Laws and Regulations Regulation of Members of the Board of Governors Number 3 of 2025 concerning the Third Amendment to Regulation of Members of the Board of Governors Number 21/18/PADG/2019 concerning the Implementation of National Standards Quick Response Code for Payments Bank Indonesia Regulation No. 17/3/PBI/2015 of 2015 concerning the Obligation to Use Rupiah in the Territory of the Unitary State of the Republic of Indonesia Constitution of the Republic of Indonesia in 1945. Law Number 7 of 2011 concerning Currency Law Number 8 of 1999 concerning Consumer Protection B. Books Ali, Zainuddin. Legal Research Methods. Jakarta: Sinar Grafika, 2022. Barkatullah, Abdul Halim. Consumer rights. Nusamedia, 2020. Joesoef, Iwan Erar, Sp N. SH, and M. Kn. Legal Theory: Dogma-Theory-Philosophy. Image Aditya Bakti, 2021. Christian, Celina Tri Siwi. Consumer protection law. Sinar Grafika, 2022. Sihombing, Agustinus. Consumer Protection Law. CV. Azka Pustaka, 2023. Sriekaningsih, Ana. QRIS and the New Era of Payment Transactions 4.0. Andi Publishers, 2020. C. Scientific Journals/Articles Alifia, Nadhifa, Erwin Permana, and Harnovinsah Harnovinsah. "Analysis of the use of QRIS on increasing MSME income." Journal of Economic Education Research 9, no. 1 (2024): 102-115. Armis, Rizkan. "Rejection of Coins by Traders in Banda Aceh City, Lueng Bata District (Study: In a Normative Review)." Journal of Justice: Journal of Law, Legislation and Social Institutions (2025): 1-15. Bhuiyan, Mohammad Rakibul Islam, Most Sadia Akter, and Saiful Islam. "How does digital payment transform society as a cashless society? An empirical study in the developing economy." Journal of Science and Technology Policy Management 16, no. 4 (2025): 756-774. Farhan, Ahmad, and Aishwari Wardani Shifa. "The use of QRIS payment methods in every MSME in the digital era." Journal of Community Service of the Archipelago 4, no. 2 (2023): 1198-1206. Fathurrahman, Raihan, Suyadi Suyadi, and Ulil Afwa. "Legal Protection of Consumers with Disabilities as Users of Air Transportation Services in the Event of Discrimination by Etihad Airways Based on Law Number 8 of 1999 concerning Consumer Protection (Case Study of Decision Number 846/Pdt.G/2016/PN Jkt.Sel)." Soedirman Law Review 4, no. 2 (2022). Febrinda, Rizky Ramadini, and Rahayu Ningsih. "Readiness for the digitalization of the non-cash payment system in the people's market." Journal of Economics and Public Policy 13, no. 2 (2023): 87-100. Kurniawti, Eris Tri, Idah Zuhroh, and Nazaruddin Malik. "Literacy and education on non-cash payments through the QR Code Indonesian Standard (QRIS) application for millennials." Economic Innovation Case Study 5, no. 01 (2021). Maharani, Alfina, and Adnand Darya Dzikra. "The Function of Consumer Protection and the Role of Consumer Protection Institutions in Indonesia: Protection, Consumers and Business Actors (Literature review)." Journal of Information Systems Management Economics 2, no. 6 (2021): 659-666. Maulidah, Alfi Rizka, Rini Puji Astuti, Khaerun Nisa, Wisnu Erlangga, and Endah Hambarwati. "Development of digital payment systems: In the era of the industrial revolution 4.0 in Indonesia." Journal of Digital Economics and Business 1, no. 4 (2024): 798-803. Mendrofa, Otniel Ogamota. "Restrictions on Religious Freedom Based on Theories of Justice and Human Rights." Milthree Law Journal 1, no. 1 (2024): 30-61. Mohd Thas Thaker, Hassanudin, Niviethan Rao Subramaniam, Abdul Qoyum, and Hafezali Iqbal Hussain. "Cashless society, e‐wallets and continuous adoption." International Journal of Finance & Economics 28, no. 3 (2023): 3349-3369. Mubarak, Dzakisyah Alyus. "Review of the Implementation of the Digital Payment Application System in the Implementation of Cashless Payments during the COVID-19 Pandemic." PhD diss., State Financial Polytechnic STAN, 2022. Mutiara, Tasya Delvita, and Lilawati Ginting. "The Unfulfillment of Consumer Rights in the Consumer Protection Law." Humantech: Indonesian Multidisciplinary Scientific Journal 2, no. 3 (2023): 598-604. Nazar, Mohammad Rafki, Utari Arifah, Serena Maharani Fitri, Syifa'Aulia Santika Putri, and Muhammad Pradiptya Ramadianto. "Analysis of Factors Influencing the Interest in the Use of Electronic Money and the Emergence of a Cashless Society in Indonesia." Scientific Journal of Educational Vehicles 9, no. 7 (2023): 287-295. Nurullia, Syafira. "Initiating the Regulation and Implementation of Central Bank Digital Currency in Indonesia: Framed ius Constituendum." Journal of Judicial Review 23, no. 2 (2021): 275-290. Rakhmawati, Aida, and Sasiska Rani. "Price discrimination based on gender: Products in Indonesia." Journal of Accounting Research Tridinanti (Jurnal Ratri) 4, no. 1 (2022): 01-12. daughter, Wirda, Andri Soemitra, and Nur Ahmadi Bi Rahmani. "The Influence of the Technolgy Acceptance Model on Student Interest in Using the Quick Response Code Indonesian Standard (QRIS) as a Cashless Society." MES Management Journal 2, no. 1 (2023): 116-126. Setyawati, Desy Ary, Dahlan Ali, and M. Nur Rasyid. "Protection for consumer rights and the responsibilities of business actors in electronic transaction agreements." Shia Kuala Law Journal 1, no. 3 (2017): 46-64. Sihaloho, Josef Evan, Atifah Ramadani, and Suci Rahmayanti. "Implementation of the Indonesian Standard Quick Response Payment System for the Development of MSMEs in Medan." Journal of Business Management 17, no. 2 (2020): 287-297. Susantri, Yulia. "Protection of Consumer Rights in a Human Rights Perspective." Constitution: Journal of State and Political Law Research 1, no. 1 (2022): 44-58. Yustisha, Ammi. "Gender-based price discrimination (Pink tax): Violations of the Consumer Protection Act." UNES Law Review 5, no. 4 (2023): 3940-3948. D. Undergraduate Thesis Adetia, Sekar Nurlaeli. "Comparative Analysis of the Success of MSMEs in Purbalingga Before and After Using the Quick Response Indonesian Standard (QRIS)." STATE ISLAMIC UNIVERSITY PROF. KH SAIFUDDIN ZUHRI. https://repository. Uinsaizu. ac. id/22379/1/Sekar Nurlaeli Adetia_Analisis Comparison of the Success of MSMEs in Purbalingga Before and After Using Quick Response Indonesian Standard% 28QRIS 29 (2023). Manaram, Karel. "Juridical Study of Refusal of Cash Payment in Buying and Selling Transactions." PhD diss., NATIONAL UNIVERSITY, 2025. E. Website News Administrator. "QRIS Transactions Soar 226.54%, Digital Payment Revolution in Indonesia." Indonesia.go.id, July 29, 2024. https://indonesia.go.id/kategori/editorial/8434/transaksi-qris-melonjak-226-54-revolusi-pembayaran-digital-di-indonesia. Retrieved on 21 May 2025 Sveriges Riksbank. Payments Report 2025. Stockholm: Sveriges Riksbank, 2025.“ The Swedish Payments Market Is Almost Entirely Digital.” https://www.riksbank.se/en-gb/payments--cash/payments-in-sweden/payments-report-2025/trends-on-the-payments-market/the-swedish-payments-market-is-almost-entirely-digital/. Diakses 24 November 2025. Tempo.co. "The History of QRIS in Indonesia to Be Used in ASEAN Countries." April 11, 2023. https://www.tempo.co/ekonomi/sejarah-qris-di-indonesia-hingga-bisa-digunakan-di-negara-asean-199154. Retrieved on 21 May 2025 Tempo.co. "Bank Indonesia Reprimands Traders Who Refuse Cash Payments: Violating the Law." October 18, 2024. https://www.tempo.co/ekonomi/bank-indonesia-tegur-pedagang-yang-menolak-pembayaran-tunai-melanggar-undang-undang-411838. Retrieved on 21 May 2025